The role of surfaceant protein A in immunity to HPV16 pseudovirus infection - Ujma, Sylvia (University of Cape Town, 2019)
Infection by oncogenic human papillomavirus (HPV) is known to be the causative agent for the development of various anogenital cancers, including cervical cancer. Worldwide, the majority of cervical cancer cases occur in less developed regions, and while prophylactic vaccines exist to combat HPV infection, they are largely unattainable in these areas. Therefore, alternative preventative measures against HPV infection are needed to help eradicate cervical cancer over time. Since HPV employs multiple mechanisms to evade the host immune response, a proposed method for preventing infection may be by enhancing HPV recognition by the immune system. Surfactant proteins A and D (SP-A and SP-D) are innate immune proteins with a variety of functions including recognition and opsonisation of pathogens. They are primarily found in the lung, but have also been shown to be expressed at other sites of the body, including the female reproductive tract. It was hypothesised that SP-A and/or SP-D may enhance immune recognition of HPV, thereby preventing infection. To assess this hypothesis, co-immunoprecipitation and flow cytometry experiments were performed to determine whether SP-A and/or SP-D bind to HPV16 pseudovirions (HPV16- PsVs). SP-A was shown to bind to HPV16-PsVs as well as enhance viral uptake by RAW264.7 murine macrophages, while SP-D bound HPV16-PsVs weakly and had no effect on viral uptake. To confirm these observations and to assess whether SP-A had an effect on HPV16- PsVs infection in vivo, a well-established, but not yet available murine HPV16-PsVs cervicovaginal challenge model system was set up at UCT. It was determined that neither naïve nor C57BL/6 mice challenged with HPV16-PsVs expressed SP-A in the female genital tract. However, under the experimental conditions established herein, pre-incubation of HPV16-PsVs with purified SP-A at a 1:10 weight per weight ratio resulted in a reduction in infection. This study is the first to describe a biochemical and functional association of HPV16 virions with the innate immune molecule SP-A. In the long term, these observations may contribute to the development of topical microbicides incorporating recombinant fragments of SP-A to reduce the burden of new HPV infections.